Evaluation of the Effectiveness of the Tap Test by Combining the Use of Functional Gait Assessment and Global Rating of Change - Kameda, Masahiro; Kajimoto, Yoshinaga; Nikaido, Yasutaka; Kambara, Akihiro; Tsujino, Kohei; Yamada, Hironori; Takagi, Fugen; Fukuo, Yusuke; Kosaka, Takuya; Kanemitsu, Takuya; Katayama, Yoshihide; Tsuji, Yuichiro; et al. (Frontiers in Neurology, 2022)
Background Although the tap test for patients with suspected idiopathic normal pressure hydrocephalus (iNPH) is still often performed as part of the preoperative evaluation, it is true that some studies have reported the limitations of the tap test, claiming that it does not provide the additional information for appropriate patient selection for surgery. We aimed to determine whether a better method of pre- and post-tap test assessment could lead to appropriate patient selection for shunting. Methods We performed the tap test as part of the preoperative evaluation in all 40 patients who underwent lumboperitoneal shunt surgery for iNPH from April 2021 to September 2021. We retrospectively analyzed the patient data. We examined whether a comprehensive evaluation of the effect of the tap test using the Functional Gait Assessment (FGA) and Global Rating of Change (GRC) scales would identify a wider range of patients who would benefit from shunt surgery than the 3-m Timed Up and Go test (TUG) alone. Results Assuming a prevalence of 1% for iNPH, the TUG had a sensitivity of 0.23, specificity of 0.71, positive likelihood ratio of 0.79, and negative likelihood ratio of 1.09. When improvement in either the FGA or the GRC was used as a criterion for the validity of the tap test, the sensitivity was 0.88, specificity was 0.17, positive likelihood ratio was 1.06, and negative likelihood ratio was 0.71. Conclusion Improvement in either the GRC or the FGA is a more sensitive criterion for the effectiveness of the tap test for the gait aspect than the TUG. Since the negative likelihood ratio is lower than that for the TUG alone, it is more appropriate to exclude patients with neither GRC nor FGA improvement from surgical indications than to exclude surgical indications based on a negative TUG.